Research capacity building through North-South-South networking: towards true partnership? An exploratory study of a network for scientific support in the field of sexual and reproductive health - K. Van der Veken; L. Belaid; T. Delvaux; V. De Brouwere (BMC, 2017)
Abstract Background We explored the perceptions of members of the Network for Scientific Support in the field of Sexual and Reproductive Health (NetSRH) on North-South-South networking and on constraints and perspectives for South-led research. Methods An exploratory qualitative study was conducted 18 months after the network was launched. In-depth interviews were carried out with NetSRH members (n = 15) affiliated to southern research institutions. A thematic analysis was done and N-Vivo 10 software used. Results A number of barriers to South-led research were identified, the most important being a lack of time, resources and research skills, and donor influence for the choice of research topics. Although the level of technical skills, such as writing proposals and scientific papers, differed among NetSRH members, all welcomed additional research capacity building. All members have deplored the lack of research management skills such as project cycle management as well as how to communicate with and get funds from donor agencies. International (local or regional) donor agencies had their own agenda with a budget already reserved for other purposes, thus priorities identified by national researchers were less taken into consideration. Systemic dependencies on external funds lead southern research partners to respond to calls for proposals mostly initiated by partners from northern institutions, leaving limited leeway for local initiatives. Southern NetSRH members perceived coaching done by the northern partners in scientific writing positively. South-South collaboration was minimal within NetSRH at this stage of the project, mainly due to time and resources constraints. Conclusion NetSRH members unanimously concluded that sustainable financing of southern research centres is a necessary condition for them to initiate their own research projects. We recommend reserving funds within the international donor agencies for South-led research in order to break the vicious circle of running behind money provided by northern donors, thereby missing out on time and resources for reviewing research gaps and/or conducting needs evaluations required to initiate relevant own research.